Personality and good business judgement: the bright and dark side of business reasoning - Furnham, Adrian; Sherman, Ryne A. (Frontiers in Psychology, 2025)
The current study explored the relationship between measures of “bright-side” and “dark-side” personality traits and business reasoning (BR)/judgment using the Hogan Business Reasoning Inventory (HBRI). Participants were a global sample (N = 2,342) who completed the Hogan Personality Inventory (HPI), a bright-side trait measure; the Hogan Development Survey (HDS), a dark-side trait measure; and the HBRI, which is similar to a measure of general cognitive ability. The analyses showed gender effects (men scored higher) but not age effects. Correlation and regression analyses showed that Learning Approach and Adjustment traits were positively associated with business reasoning, while Prudence and Inquisitive traits were negatively associated with business reasoning. In cases where significant dark-side factor relationships were observed, they were negatively associated with business reasoning, except for Reserved and Imaginative traits. However, these traits accounted for relatively little of the variance (approximately 5%) in business reasoning. Stable, ambitious, and intellectually curious individuals who are not high on Conscientiousness and have few dark-side traits appear to be better at business reasoning.